Back Matter Jurnal Litbang Industri Vol. 11 No. 2 Desember Tahun 2021 - Salamariza Sy (Institution for Industrial Research and Standardization of Industry - Padang, 2021)
Back Matter Jurnal Litbang Industri Vol. 11 No. 2 Desember Tahun 2021